Governance and power in the metropolitan regions of the Randstad - Spaans, Marjolein; Zonneveld, Wil; Stead, Dominic (AESOP, 2019)
Urban growth and new patterns of urban flows demand new scales and forms of governance since administrative borders often do not reflect contemporary functional relations such as labour and housing markets. To address these issues, new arrangements for metropolitan governance have been developed across many countries. These arrangements can take many forms but often seek to reduce administrative fragmentation and manage complex issues beyond the municipal scale. These arrangements are often collaborative and negotiated; competences and processes of deliberation and decision-making are not closely defined by the rule of law. Their strategic capacity or powers are derived from ‘resources’, ‘process’ and ‘meaning’. This paper compares these three types of power in the governance arrangements for two Dutch metropolitan areas: Amsterdam and Rotterdam The Hague.
Keywords: Metropolitan regions; governance; power; Randstad